Identification of Ζ-crystallin/NADPH:quinone reductase as a renal glutaminase mRNA pH-responsive element binding protein - Tang, Aimin, author; Curthoys, N. P., advisor; Bamburg, James R., committee member; Laybourn, Paul, committee member; Woody, Robert W., committee member; Mykles, Donald L., committee member (Colorado State University. Libraries, 2001)
During chronic metabolic acidosis, glutamine metabolism increases significantly in rat kidney. This adaptation results in an increase in ammoniagenesis and gluconeogenesis, which facilitate excretion of acid and restoration of blood pH. This response is sustained, in part, by a selective stabilization of glutaminase (GA) mRNA. Previous studies identified an AU-rich element (AURE) located within the 3'-UTR of the GA mRNA. Expression of various chimeric mRNAs in the LLC-PK1-F- cells demonstrated that the AURE is both necessary and sufficient to impart a pH-responsive stabilization, and is therefore considered a pH-responsive element (pHRE). Using RNAEMSA, this pHRE was found to bind to a cytosolic protein with a high affinity and specificity. A biotinylated oligoribonucleotide containing the pHRE was used as an affinity ligand to purify a 36-kDa protein from rat renal cortex that exhibited the same specific binding properties as observed with crude cytosolic extracts. MS/MS micorsequencing identified multiple peptides that were either identical or highly homologous to mouse ζ-crystallin/NADPH:quinone reductase. Antiserum against ζ-crystallin cross-reacts with the purified protein. This serum also blocks the formation of the protein/RNA complex between the pHRE and a crude extract. Bacterially expressed recombinant ζ-crystallin was purified, but it failed to form a complex with pHRE. However, there was indication that this protein, when expressed in LLC-PK1-F-. retained the affinity to pHRE. Thus, the combined data indicate that ζ-crystallin is the rat renal GA mRNA pH-responsive element binding protein (pHRE-BP).
Keywords: biochemistry; molecular biology